Quantitative Easing, Investment, and Safe Assets: The Corporate-Bond Lending Channel - Erasmo Giambona; Rafael Matta; José-Luis Peydró; Ye Wang (ZBW – Leibniz Information Centre for Economics, 2020)
We show that Quantitative Easing (QE) stimulates investment via a corporate-bond lending channel. Fed's large-scale purchases of MBS and treasuries creates a vacuum of safe assets, prompting safer firms to invest by issuing relatively "safe" bonds. Using micro-data around QE, we find that QE increases firm-level investment by 7.4 percentage points for firms with bond market access. Results hold excluding the financial crisis period. This growth is financed with senior bonds. We find no evidence of higher shareholders' payouts. The robust findings support a stylized model in which reducing the supply of treasuries lowers "safe" corporate bond yields, stimulating investment.
Keywords: E5; G01; G31; G32; G38; 330; Quantitative Easing; Corporate-Bond Lending Channel; Investment; Safe Assets; Financing